2009
DOI: 10.1007/s11192-007-2043-y
|View full text |Cite
|
Sign up to set email alerts
|

International scientific collaboration of China with the G7 countries

Abstract: Collaboration is one of the remarkable characteristics of contemporary basic research. Using bibliometric method, we quantitatively analyze international collaboration publication output between China and the G7 countries based on Science Citation Index. The results indicate that international collaboration publication output between China and the G7 countries has shown exponential growth aroused by the growth of science in China. USA is the most important collaboration country and the international collaborat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
82
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(83 citation statements)
references
References 29 publications
1
82
0
Order By: Relevance
“…But, as is clear in the Brazilian case, the increase in the amount of products increases the likelihood of citation. Even though these variables might be important, the cluster result reported by different variables indicates the importance of different aspects of interest in the international collaboration with developing countries (He, 2009).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…But, as is clear in the Brazilian case, the increase in the amount of products increases the likelihood of citation. Even though these variables might be important, the cluster result reported by different variables indicates the importance of different aspects of interest in the international collaboration with developing countries (He, 2009).…”
Section: Discussionmentioning
confidence: 97%
“…Collaboration among these countries could have increased over time in more traditional areas of science (biology, chemistry, engineering, clinical and neuroscience) but not necessarily have the same levels of interaction, despite regularizing variables such as language. He (2009) showed how in the case of China this collaboration does not necessarily foster the impact of these publications, which would show other factors such as currents of thinking (main stream) or the interest in social scientific topics as possible mechanisms that stimulate collaboration. However, Bordons et al (1996) showed how in the area of biology different patterns of collaboration can exist.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…China, Israel, the Netherlands and Switzerland had higher share of internationally collaborated papers. He 9 examined international collaboration of G7 countries with China and found that US was the major collaborator of China among all the G7 countries.…”
Section: Review Of Literaturementioning
confidence: 99%
“…The eight major industrialized countries G8, ranked in the top 11 in Table 4, had 59% over the investigation period. Similarly, the seven major industrialized countries G7 the USA, Germany, the UK, Japan, France, Canada, and Italy accounted for a significant proportion exited in many researches (Li et al, 2009;He, 2009;Fu et al, 2010;Wang et al, 2010). The USA dominated, ranking 1 st in independent and collaborative articles, as well as first author and corresponding author articles.…”
Section: Characteristics Of Top 20 Countries/territoriesmentioning
confidence: 99%